Answer:
The first space is 3,
The second space is -2
The third space is 100
Step-by-step explanation:
A circle with center (a, b) and has radius r has equation: ![(x-a)^{2} + (y-b)^{2} = r^{2}](https://tex.z-dn.net/?f=%28x-a%29%5E%7B2%7D%20%2B%20%28y-b%29%5E%7B2%7D%20%3D%20r%5E%7B2%7D)
Now, if the circle passes through (-3, 2) and it has center on (5, -4). That means the radius of the circle will be the distance between points (-3, 2) and (5, -4).
![d = \sqrt{(x_{2} - x_{1} )^{2} + (y_{2} - y_{1} )^{2} }](https://tex.z-dn.net/?f=d%20%3D%20%5Csqrt%7B%28x_%7B2%7D%20-%20x_%7B1%7D%20%29%5E%7B2%7D%20%2B%20%28y_%7B2%7D%20-%20y_%7B1%7D%20%29%5E%7B2%7D%20%7D)
where d = formula of distance between points ![(x_{2}, y_{2} ) \ and \ (x_{1}, y_{1} )](https://tex.z-dn.net/?f=%28x_%7B2%7D%2C%20y_%7B2%7D%20%29%20%5C%20and%20%5C%20%28x_%7B1%7D%2C%20y_%7B1%7D%20%29)
![d = \sqrt{(-3-5)^{2} + (-4-2)^{2} }\\ d = \sqrt{-8^{2} + -6^{2} }\\ d = \sqrt{64+36}\\ d = \sqrt{100}\\ d = radius \ of \ circle = 10](https://tex.z-dn.net/?f=d%20%3D%20%5Csqrt%7B%28-3-5%29%5E%7B2%7D%20%2B%20%28-4-2%29%5E%7B2%7D%20%20%7D%5C%5C%20d%20%3D%20%5Csqrt%7B-8%5E%7B2%7D%20%2B%20%20-6%5E%7B2%7D%20%7D%5C%5C%20d%20%3D%20%5Csqrt%7B64%2B36%7D%5C%5C%20d%20%3D%20%5Csqrt%7B100%7D%5C%5C%20d%20%3D%20radius%20%5C%20of%20%5C%20circle%20%3D%2010)
Now, with r = 10, a = -3, b = 2
The equation of circle becomes:
![(x-(-3))^{2} + (y-2)^{2} = 10^{2} \\(x+3)^{2} + (y-2)^{2} = 100 \\](https://tex.z-dn.net/?f=%28x-%28-3%29%29%5E%7B2%7D%20%2B%20%28y-2%29%5E%7B2%7D%20%20%3D%2010%5E%7B2%7D%20%5C%5C%28x%2B3%29%5E%7B2%7D%20%2B%20%28y-2%29%5E%7B2%7D%20%20%3D%20100%20%5C%5C)
The first space is 3,
The second space is -2
The third space is 100